Fire Alarm Application with Short Message Service (SMS) and Arduino FOR Reminder Information Display System in Puri Permai Tbk Housing - M. Subchan; Aza Azhari (Institute of Computer Science (IOCS), 2021)
Security disturbances do not only come from people who will do bad things but from other factors as well, for example the occurrence of fires which is a threat to us. Fire disasters can occur at any time regardless of time or place. The fire disaster will definitely cause damage, loss, maybe even casualties. If this happens in a government agency / office, then the loss incurred is the loss of important / valuable documents, thus affecting the implementation of daily tasks. So fire prevention and control is important. This prototyping method will produce a system prototype as an intermediary for developers and users in order to interact in the process of information system development activities. In order for the prototype making process to be successful, it is by defining the rules at an early stage, namely the developer and the user must have an understanding that the prototype was built to define initial requirements. When mQ2 detects smoke and the flame sensor detects a fire, then the buzzer turns on. Sim800l successfully sends a message when mQ2 detects smoke and the flame sensor detects a fire.